1996
DOI: 10.1021/jo960133w
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism of Xanthine Oxidase Substrates Hypoxanthine and Allopurinol

Abstract: The tautomerism of neutral hypoxanthine and allopurinol in the gas phase and in aqueous solution has been examined by theoretical methods. The tautomeric equilibrium in the gas phase was studied from semiempirical and ab initio quantum mechanics (QM) and also from density functional theory (DFT) calculations. Electron correlation effects were included in ab initio computations at the Møller−Plesset level, and DFT calculations were carried out using the Becke3−Lee−Yang−Parr functional. The influence of the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
76
2
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 71 publications
9
76
2
4
Order By: Relevance
“…Theoretical and experimental observations have shown that the keto form predominates in the gas phase. 5,7,9,10,[21][22][23] For example, the valance photoelectron spectra of HYP, XAN, and CAFF, recorded by Feyer et al 9 at 100 eV photon energy are similar. Considering that CAFF has a single keto tautomer form, it can be concluded that this form is more stable in the gas phase, for HYP and XAN.…”
Section: Equilibrium Structures and Hartree2fock Molecular Orbitalsmentioning
confidence: 86%
See 2 more Smart Citations
“…Theoretical and experimental observations have shown that the keto form predominates in the gas phase. 5,7,9,10,[21][22][23] For example, the valance photoelectron spectra of HYP, XAN, and CAFF, recorded by Feyer et al 9 at 100 eV photon energy are similar. Considering that CAFF has a single keto tautomer form, it can be concluded that this form is more stable in the gas phase, for HYP and XAN.…”
Section: Equilibrium Structures and Hartree2fock Molecular Orbitalsmentioning
confidence: 86%
“…Additionally, highly expensive ab initio calculations have shown that the amount of enol tautomers is negligible in comparison with keto forms for HYP and XAN in gas phase. [21][22][23] In this work and based on the above observations, the keto tautomers of each compound have been considered for direct SAC-CI calculations.…”
Section: Equilibrium Structures and Hartree2fock Molecular Orbitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is supported by results of UV 19,21 , IR 17,18 , Raman 29 , 1H NMR 19 and 13C NMR 19,23 spectroscopies, and X-ray analysis 24 . Pullman and Pullman 28 have investigated the tautomerism of oxopurines by the theoretical CNDO/2 method and three groups of authors [29][30][31] have reported ab initio quantum mechanical calculations using 6-31G(d), 6-31G(d,p), or MIDI basis sets. Contreras and Alderete 32 used the semiempirical AM1 and MNDO methods to calculate the structure, bondorder matrices, localized MOs, and IR spectra for the tautomers of hypoxanthine in the gas phase.…”
mentioning
confidence: 56%
“…In addition, knowing how these tautomerization energies change in different environments can provide insight into the influence of solvent effects on molecular stability. The physicochemical properties of the tautomerism of hypoxanthine have been investigated experimentally [17][18][19][20][21][22][23][24][25][26][27] and theoretically [28][29][30][31][32] . In a wide variety of environments, including the gas phase, keto tautomers of hypoxan thine are most stable.…”
mentioning
confidence: 99%